Successful conservative management of viable caesarean scar pregnancy with systemically administered methotrexate followed by ultrasound guided ethanol ablation of gestational sac: a rare case report - Muthukrishnan, Dharini; Janakiraman, Prabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
The incidence and diagnosis of caesarean scar pregnancy is on rise because of rising caesarean section rates. Though many modalities are available for its management, none seems to be superior and data regarding them are also lacking. Here we are presenting a rare case report of successful conservative management of viable caesarean scar pregnancy with systemic methotrexate followed by ultrasound guided ethanol ablation of gestational sac.